Suffering as an independent component of the experience of pain. (7th April 2015) - Bustan, S.; Gonzalez‐Roldan, A.M.; Kamping, S.; Brunner, M.; Löffler, M.; Flor, H.; Anton, F.
Abstract Background Pain has consistently been viewed as containing two dimensions, a sensory (intensity) and an emotional (unpleasantness). It has been suggested that pain involves higher order cognitive processes that go beyond unpleasantness. We therefore aimed at extending the assessment of pain by introducing an additional dimension of pain‐related suffering and identifying noxious stimulation protocols that are most adequate for its psychophysical and psychophysiological characterization. Methods Twenty‐four healthy volunteers received separate series of tonic and phasic noxious mechanical stimuli. Visual analogue scales were used to rate intensity, unpleasantness and suffering and psychophysiological measurements such as heart rate, skin conductance and corrugator electromyography were recorded. Acoustically evoked startle responses were measured in part of the assessments to obtain additional indicators of pain aversiveness. Results Spearman's correlation coefficients and partial correlations analyses as well as principal component analyses confirmed that suffering constitutes an integral component of pain processing that is distinct from intensity and unpleasantness. Tonic, rather than phasic, stimulation method was more effective in eliciting pain and suffering and under this condition startle responses where higher during long compared to short stimuli. Conclusions These results suggest that in acute pain, suffering is a constitutive dimension that might even be more crucial in clinical states of pain.